Development of AR-based Diorama to Improve Critical Reasoning Dimension and Learning Outcomes of Fourth-Grade Elementary School Students - Emiliana Catherine Corneliesta; Kurotul Aeni; Yusuff Bolaji Yusuff (Al Ibtida: Jurnal Pendidikan Guru MI, 2025)
AbstractThis research is motivated by teachers who have not used digital learning media, resulting in low critical reasoning and learning outcomes. The purpose of the research is to develop a design and test the feasibility and effectiveness of augmented reality-based diorama media to improve critical reasoning dimensions and learning outcomes of Pancasila education. This study uses the research and development method, specifically the ADDIE model, to create augmented reality-based diorama media for Pancasila education aimed at fourth-grade students at Public Elementary School (SDN) Kalibanteng Kidul 01 in Semarang City, Central Java. The study found that the media is highly suitable for education, with validation scores of 93.33% from media experts and 98.21% from material experts. The assessment of critical reasoning scored 95.24%. The t-test results supported the hypothesis, showing significant effectiveness with an N-gain score of 0.7901, classifying it as high. Overall, the study concludes that the augmented reality-based diorama media are effective in improving critical reasoning and learning outcomes related to Pancasila principles for these students in class IV, SDN Kalibanteng Kidul 01, Semarang City, Central Java.Keywords: augmented reality, critical reasoning dimension, diorama, learning           outcomes. AbstrakPenelitian ini dimotivasi oleh guru yang belum menggunakan media pembelajaran digital, sehingga mengakibatkan rendahnya penalaran kritis dan hasil belajar. Tujuan penelitian ini adalah untuk mengembangkan desain dan menguji kelayakan serta efektivitas media diorama berbasis augmented reality untuk meningkatkan dimensi penalaran kritis dan hasil belajar pendidikan Pancasila. Studi ini menggunakan metode penelitian dan pengembangan, khususnya model ADDIE, untuk menciptakan media diorama berbasis augmented reality untuk pendidikan Pancasila yang ditujukan untuk siswa kelas empat di SDN Kalibanteng Kidul 01 di Kota Semarang, Jawa Tengah. Studi ini menemukan bahwa media tersebut sangat cocok untuk pendidikan, dengan skor validasi 93,33% dari pakar media dan 98,21% dari pakar materi. Penilaian penalaran kritis mendapat skor 95,24%. Hasil uji-t mendukung hipotesis, menunjukkan efektivitas yang signifikan dengan skor N-gain 0,7901, yang mengklasifikasikannya sebagai tinggi. Secara keseluruhan, penelitian ini menyimpulkan bahwa media diorama berbasis augmented reality efektif dalam meningkatkan penalaran kritis dan hasil belajar terkait prinsip-prinsip Pancasila bagi siswa kelas IV SDN Kalibanteng Kidul 01, Kota Semarang, Jawa Tengah.Kata kunci: augmented reality, dimensi bernalar kritis, diorama, hasil belajar.